An investigation study of academic writing problems faced by Arab speaking postgraduate at Universiti Teknologi Malaysia (UTM) - Abdulkareem, Mustafa N. (2012)
This study aimed to investigate the academic writing problems encountered by Arab speaking postgraduate students at Universiti Technologi Malaysia (UTM). There are two research questions of this study. The first question involved the identification of mistakes that Arab speaking postgraduate students commit in academic writing at UTM. The second question dealt with the problems Arab speaking students’ perceived in academic writing. The data for the study were collected through distributing a set of questionnaires and writing task. The respondents of this study were 85 Arab speaking postgraduate students who come from different Arabic countries like Iraq, Yemen, Sudan, Saudi Arabia, Algeria, Libya, Palestine, and Syria who enrolled for the academic session of 2012/2012. A snowballing technique was used to determine the samples of this study. A set of the questionnaires were distributed to 80 of the respondents to reveal their opinions towards the causes of academic writing problems. Another 5 students were given a writing task which was to write two short paragraphs regarding their fields of works. The students’ writing was sent to an expert of English language to identify the mistakes made by the students. The results of their writing revealed that they made mistakes in sentence structure (53.8%), vocabulary (30.7%), and expressing their ideas (7.6%). The students also expressed their opinions with different levels of agreement regarding the causes of their academic writing problems. They expressed their opinions as being high when asked about vocabulary items (mean = 1.5) but the other questions resulted in mean scores that ranged from moderate to low, which indicate that they do not have much problems in academic writing. The findings of the study nevertheless could be used to recommend effective teaching approaches to teach academic writing that are currently used by English language teachers and v specialists.